EXAMINING MARKET ACCEPTANCE: SUSTAINABLE APPROACHES TO NEW FOOD PRODUCT DEVELOPMENT - Michael Ricky Sondak (Jurnal Manajemen Pemasaran, 2024)
This research endeavors to ascertain whether family businesses employ new product development as a strategy that is well received by the market. This qualitative research examined the food and beverage family business in Surabaya. Data was collected from credentialed persons or expertise via the use of purposive sampling. Interviews served as the primary method of data collection. The present study examines the experiences of family business proprietors in the food and beverage industry who, in response to ineffective marketing strategies, initiated the creation of innovative products. This study emphasizes sensory enjoyment, economic value, and brand trust in product development.